Education Management Strategies for Internalizing Moderate Religious Values in Learning Quran, Hadith, and Aqeedah Akhlaq in Madrasah Ibtidaiyah - Pangastuti, Ratna; Suyudi, H. M.; Bahtiar, Machfudz; Erfansyah, Nasrul Fuad; Abdullah, Zaini (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze education management strategies in internalizing moderate religious values, nationalism, tolerance, and non-violence at Madrasah Ibtidaiyah (MI) Safinda and MI Bina Bangsa. The managerial approach is structured and comprehensive, involving three main stages: value transformation, value transaction, and value internalization. The research used qualitative methods with in-depth interviews, participatory observation, and document analysis. The results showed that the managerial strategies implemented were successful in shaping students' characters. Value transformation through material delivery and advice by educators, as well as value transactions through exemplary activities such as flag ceremonies and small group discussions, are effective in instilling the values taught. Value internalization is reflected in students' daily behaviors that show nationalism, tolerance, and non-violence. The study also highlights the importance of the role of educators as models who provide real examples of these values, as well as the importance of social interaction and real experiences in the learning process. Despite limitations in generalizability and qualitative methods, this study makes an important contribution to the development of effective character education programs in madrasahs and other educational institutions. The practical implications of the findings can be used to improve the quality of character education in madrasahs